A graphene-based composite material, its preparation method and application
Patent Information
- Application Number
- CN202511614112.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2045-11-06
AI Technical Summary
但是稀土元素材料成本较高,且对电池的性能提升有限;真空化成技术需要专业的真空设备,设备采购成本高昂,且在实施过程中的工艺参数控制需要极为严格,操作复杂
[0076]优选的酸洗条件能去除负极材料表面的氧化层,暴露活性位点。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid battery technology, and in particular to a graphene-based composite material, its preparation method, and its application. Background Technology
[0002] Lead-acid batteries are widely used in transportation, communications, and energy storage due to their low cost, excellent charge / discharge performance, and mature recycling system. They are found in vehicle starting systems, backup power for communication base stations, and distributed renewable energy storage. In terms of market share, their annual sales reach hundreds of billions of dollars, accounting for over 40% of the secondary battery market, especially dominating the civilian sector in developing countries. Lead-acid batteries remain the most reliable, safest, and most economical power source. To date, no newly developed battery type (such as lithium-ion and nickel-metal hydride batteries) has achieved the commercial success of lead-acid batteries. Lead-acid batteries are one of the most widely used rechargeable batteries in solar energy, inverters, automobiles, and even hybrid and electric vehicles, providing energy at 2-3 times the cost of other types of secondary power sources.
[0003] Currently, existing lead-acid batteries suffer from problems such as high hydrogen evolution rates, poor conductivity, and short lifespan. To address these issues, researchers have added rare earth elements to grid alloy materials to enhance grid conductivity and suppress hydrogen evolution reactions; others have employed vacuum formation technology to shorten formation time, improve electrode uniformity, and ensure battery lifespan. However, rare earth element materials are expensive and offer limited performance improvements; vacuum formation technology requires specialized vacuum equipment, which is costly to purchase, and the process parameters must be strictly controlled, making the operation complex. To address the problems of high cost, complex operation, and limited performance improvement in existing technologies, this invention provides a negative electrode material and its preparation method to solve the problems of severe hydrogen evolution, poor conductivity, and short battery lifespan in existing lead-acid batteries. Summary of the Invention
[0004] In view of this, the present invention provides a graphene-based composite material, its preparation method, and its application. The graphene-based composite material provided by the present invention, through rational design of its composition and ratio, when applied to anode materials, can significantly reduce the hydrogen evolution rate and internal resistance of the anode, thereby improving the cycle performance of the battery.
[0005] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: This invention provides a graphene-based composite material comprising the following components: a graphene-CNTs three-dimensional composite framework and tin dioxide and titanium dioxide loaded on the graphene-CNTs three-dimensional composite framework; The graphene-CNTs three-dimensional composite framework was obtained by depositing carbon nanotubes on the graphene surface.
[0006] Currently, researchers have studied graphene and carbon nanotubes (CNTs), but most studies involve physical mixtures of the two materials. During physical mixing, CNTs and graphene are prone to agglomeration. When this mixture is used as an anode material, it leads to discontinuous conductive networks during conduction, resulting in high interfacial impedance. Furthermore, the CNTs are only physically adsorbed onto the interface of the anode material, making them susceptible to detachment during battery operation. Therefore, there is an urgent need to develop a new anode material to address the problems of severe hydrogen evolution, poor conductivity, and short battery life in existing lead-acid batteries.
[0007] Compared to existing technologies, the graphene-CNTs three-dimensional composite framework provided by this invention is obtained by depositing carbon nanotubes on the graphene surface. This invention employs an in-situ growth method to prepare the graphene-CNTs three-dimensional composite framework, where CNTs are vertically or entangled on the surface and within the pores of the graphene sheet structure. The two-dimensional layered structure of graphene and the one-dimensional nanostructure of CNTs intertwine and combine to form a highly efficient three-dimensional conductive network, significantly reducing the internal resistance of the negative electrode material and improving the conductivity and cycle capacity retention of the negative electrode. Secondly, in the three-dimensional composite framework structure prepared by a specific method, CNTs and graphene form stable covalent bonds, thereby improving the interfacial bonding strength of the graphene-based composite material, reducing interfacial resistance, lowering the hydrogen evolution rate of the negative electrode, and significantly improving the cycle stability of the battery. Furthermore, the graphene-CNTs three-dimensional composite framework provided by this invention has a high specific surface area, allowing tin dioxide and titanium dioxide to be uniformly and maximally dispersed on the surface and within the pores of the graphene-CNTs three-dimensional composite framework, further enhancing battery performance.
[0008] This invention adds tin dioxide and titanium dioxide to a graphene-based composite material. Tin dioxide can regulate the electronic state and adsorption environment on the surface of the negative electrode material, reducing the hydrogen evolution rate. Titanium dioxide has excellent structural stability, which not only enhances the conductivity of the negative electrode but also improves its mechanical strength. More importantly, titanium dioxide can also suppress the volume expansion problem that tin dioxide is prone to during charge-discharge cycles. The two together encapsulate and support the framework, forming a stable interface layer, effectively suppressing the recrystallization of lead sulfate and improving the cycle stability of the battery.
[0009] The graphene-based composite material provided by this invention, with its graphene-CNTs three-dimensional composite framework, possesses excellent electrical conductivity and mechanical strength. It not only significantly reduces the resistivity of the negative electrode plate but also provides structural support, enhancing the bonding force between lead powder and the negative electrode metal grid, thereby reducing the shedding of active materials and improving the cycle stability of the battery. Furthermore, this invention introduces tin dioxide and titanium dioxide into the graphene-based composite material, which form a multi-level synergistic system with the graphene-CNTs three-dimensional composite framework. This effectively solves the problems of easy hydrogen evolution, insufficient conductivity, and active material shedding in lead-acid battery negative electrodes, significantly improving the battery's cycle performance.
[0010] Preferably, the mass ratio of the graphene-CNTs three-dimensional composite framework, tin dioxide, and titanium dioxide is (92~97):(5~7):(0.5~1).
[0011] This invention further limits the ratio of graphene-CNTs three-dimensional composite framework, tin dioxide, and titanium dioxide to maximize the synergistic effect between the substances, thereby reducing the hydrogen evolution rate and internal resistance of the negative electrode and improving the cycle stability of the battery.
[0012] Preferably, the preparation of the graphene-CNTs three-dimensional composite framework includes the following steps: S100. Graphene is grown on a foam board using CVD at 1000℃~1050℃ to obtain a primary treated foam board. S200: At 60℃~80℃, the primary treated foam board is etched using an etching solution to obtain graphene. S300. Under bimetallic catalyst conditions, acetylene is introduced at 700℃~720℃ to grow carbon nanotubes on the graphene, thereby obtaining the graphene-CNTs three-dimensional composite framework.
[0013] In the graphene-CNTs three-dimensional composite framework provided by this invention, in step S100, graphene is grown at a specific temperature, which ensures that the graphene has excellent crystallinity and improves its conductivity. In addition, using a foam board as a deposition substrate enables the obtained graphene to form a continuous initial structure with certain gaps, providing a basis for subsequent composites. In step S300, acetylene is introduced at a specific temperature, which can precisely control the CNTs to be perpendicular or wrapped around the surface and pores of the graphene sheet structure, thereby giving the obtained graphene-CNTs three-dimensional composite framework excellent conductivity and mechanical strength. Its application in anode materials can significantly improve battery performance.
[0014] Preferably, in S100, the foam board is nickel foam.
[0015] Preferably, in S100, the thickness of the foam board is 0.5mm to 1mm, and the porosity is 95% to 98%.
[0016] Preferably, in S100, the foam board also needs to be pretreated. Specifically, the foam board is placed in a solvent for ultrasonic treatment, and then annealed in an H2 and Ar atmosphere.
[0017] By subjecting the foam board to ultrasonic treatment and annealing, organic matter on the surface of the foam board can be removed to the greatest extent, which is conducive to the uniform growth of graphene in the future.
[0018] It should be further noted that in S100, the solvent is at least one of acetone, ethanol, or water.
[0019] More preferably, in S100, the conditions for ultrasonic treatment are: power of 200W~500W, frequency of 40kHz, and time of 15min~18min.
[0020] More preferably, in S100, the volume ratio of H2 to Ar is 1:(3~3.5).
[0021] More preferably, in S100, the annealing temperature is 800℃~810℃.
[0022] More preferably, in S100, the annealing time is 30 min to 35 min.
[0023] Preferably, the specific operation of S100 is as follows: at 1000℃~1050℃, hydrogen and methane are introduced, and graphene is grown on the foam board by CVD method to obtain the primary treated foam board.
[0024] More preferably, in S100, the flow rate of the hydrogen gas is 50 sccm to 100 sccm.
[0025] More preferably, in S100, the flow rate of methane is 10 sccm to 20 sccm.
[0026] Preferably, in S100, the growth time is 10 min to 30 min.
[0027] It should be further noted that in S100, during the growth process, deposition needs to be carried out in an Ar atmosphere, with an Ar flow rate of 500 sccm~520 sccm.
[0028] Preferably, in S200, the etching solution is a mixed aqueous solution containing hydrochloric acid and ferric chloride.
[0029] Preferably, in S200, the concentration of ferric chloride in the mixed aqueous solution is 2.8 mol / L to 3.2 mol / L.
[0030] Preferably, in S200, the concentration of hydrochloric acid in the mixed aqueous solution is 0.1 mol / L to 0.3 mol / L.
[0031] Preferably, in S200, the etching time is 12h~24h.
[0032] Preferably, in step S200, the primary treated foam board after etching is dialyzed to neutral using deionized water and then freeze-dried to obtain the graphene.
[0033] More preferably, in S200, the freeze-drying conditions are: a temperature of -50℃ to -48℃.
[0034] Preferably, in S200, the mass ratio of the etching solution to the primary treatment foam board is (10~20):1.
[0035] Preferably, in S300, the bimetallic catalyst is an Fe-Co catalyst.
[0036] More preferably, in S300, the molar ratio of iron to cobalt in the bimetallic catalyst is 1:(1~2).
[0037] Preferably, in S300, the flow rate of the acetylene is 20 sccm to 50 sccm.
[0038] Preferably, in S300, the mass ratio of the bimetallic catalyst to graphene is (0.5~2):100.
[0039] Preferably, in S300, the growth time is 10 min to 30 min.
[0040] This invention provides a method for preparing the above-mentioned graphene-based composite material, comprising the following steps: Step 1: Add the graphene-CNTs three-dimensional composite framework and nonionic surfactant to an ethanol aqueous solution containing soluble tin salt and soluble titanium salt, adjust the pH to acidic, impregnate at -0.2MPa to -0.1MPa, release the pressure, and dry at -50℃ to -48℃ to obtain the first-treated graphene-CNTs three-dimensional composite framework system. Step 2: At 0℃~5℃, the first treated graphene-CNTs three-dimensional composite framework system is added to a boron-containing reducing agent solution for reaction, washed, annealed at 60℃~70℃, and then heated to 300℃~320℃ for oxidation reaction to obtain graphene-based composite material.
[0041] Currently, when loading tin dioxide onto graphene / CNTs, a hydrothermal synthesis method is commonly used to synthesize tin dioxide, which is then bonded to graphene / CNTs via van der Waals forces or hydrogen bonds. However, when the tin dioxide-graphene-based composite material prepared by this method is used in batteries, it is prone to detachment during cycling, thereby reducing the battery's cycle performance and conductivity. The inventors have abandoned the traditional hydrothermal synthesis method and adopted an impregnation-chemical reduction method to prepare tin dioxide and titanium dioxide on a graphene-CNTs three-dimensional composite framework. Soluble tin salts and soluble titanium salts are impregnated and adsorbed onto the surface and pores of the graphene-CNTs three-dimensional composite framework under specific pressure. Further annealing at a specific temperature results in a strong interfacial bond between the tin dioxide and the graphene-CNTs three-dimensional composite framework, further improving the battery's cycle stability and conductivity, and also reducing the hydrogen evolution rate at the negative electrode.
[0042] Preferably, in step 1, the soluble tin salt is SnCl2.
[0043] Preferably, in step 1, the soluble titanium salt is Ti(SO4)2.
[0044] It should be further noted that in step 1, the ethanol-water solution containing soluble tin salt and soluble titanium salt is prepared separately, specifically including the following steps: Soluble tin salts are dissolved in an aqueous ethanol solution to obtain an aqueous ethanol solution containing soluble tin salts. Soluble titanium salts are dissolved in an aqueous ethanol solution to obtain an aqueous ethanol solution containing soluble titanium salts. An aqueous ethanol solution containing soluble tin salt and an aqueous ethanol solution containing soluble titanium salt are mixed evenly to obtain the aqueous ethanol solution containing soluble tin salt and soluble titanium salt.
[0045] It should be further noted that in the ethanol aqueous solution containing soluble tin salt and the ethanol aqueous solution containing soluble titanium salt, the volume ratio of ethanol to water is 1:(0.9~1.1).
[0046] It should be further noted that the concentration of the soluble tin salt in the ethanol aqueous solution containing the soluble tin salt is 0.1 mol / L to 0.2 mol / L.
[0047] Preferably, in step 1, the concentration of the soluble titanium salt in the ethanol aqueous solution containing the soluble titanium salt is 0.025 mol / L to 0.03 mol / L.
[0048] Preferably, in step 1, the nonionic surfactant is polyvinylpyrrolidone.
[0049] More preferably, in step 1, the amount of the nonionic surfactant added is 0.5% to 0.6% of the mass of the ethanol aqueous solution.
[0050] It should be further noted that in step 1, the pH is adjusted to 2-3 using a 0.1mol / L~0.2mol / L hydrochloric acid aqueous solution.
[0051] Preferably, in step 1, the soaking time is 2h to 2.5h.
[0052] It should be further explained that in step 1, the graphene-CNTs three-dimensional composite framework is added to an ethanol aqueous solution containing soluble tin salt and soluble titanium salt, and then impregnated under conditions of -0.2MPa to -0.1MPa for 2 to 2.5 hours.
[0053] By evacuating the air under specific pressure conditions for 2 to 2.5 hours, the gas inside the pores of the graphene-CNTs three-dimensional composite framework can be completely removed, allowing the solute in the ethanol aqueous solution to completely permeate into the pores.
[0054] It should be further explained that in step 1, the pressure is released to atmospheric pressure at a rate of 0.01 MPa / min to 0.02 MPa / min.
[0055] Preferably, in step 1, the drying temperature is -50℃ to -48℃, and the time is 2h to 2.5h.
[0056] Preferably, in step 2, the boron-containing reducing agent solution is a sodium borohydride solution.
[0057] Preferably, in step 2, the reaction time is 1 h to 1.5 h.
[0058] Preferably, in step 2, the mass ratio of the first treated graphene-CNTs three-dimensional composite framework system to the boron-containing reducing agent solution is 1:(10~20), and the concentration of the boron-containing reducing agent solution is 0.2mol / L~0.4mol / L.
[0059] It should be further noted that in step 2, the solution needs to be washed with water until it is neutral.
[0060] Preferably, in step 2, the annealing time is 2h~2.5h.
[0061] Preferably, in step 2, the oxidation reaction takes 2 to 2.5 hours.
[0062] It should be further noted that in step 2, the heating rate is no longer limited, and conventional technical means can be used to heat the temperature to 300℃~320℃.
[0063] The present invention provides a negative electrode material comprising the following components in parts by mass: 20-22 parts lead powder and 1 part graphene-based composite material.
[0064] This invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: The graphene-based composite material and lead powder are mixed evenly, and the mixture is kept at 280℃~300℃ for the first heat preservation. Then, the temperature is raised to 320℃~340℃ for the second heat preservation. After cooling, acid washing, and drying, the negative electrode material is obtained.
[0065] The method for preparing the negative electrode material provided by this invention involves two heat treatments at a specific temperature, which can improve the interfacial bonding between the graphene-based composite material and lead powder, further improve the cycle performance and conductivity of the battery, and reduce the hydrogen evolution rate.
[0066] It should be further explained that the specific operation of uniformly mixing the graphene-based composite material and lead powder includes: uniformly mixing the graphene-based composite material, lead powder and dispersant, and ball milling.
[0067] For example, the dispersant is stearic acid.
[0068] For example, the amount of dispersant added is 0.5% to 0.8% of the sum of the mass of the graphene-based composite material and the lead powder.
[0069] For example, the ball mill rotates at a speed of 500 rpm to 600 rpm.
[0070] For example, the ball milling time is 2h to 2.5h.
[0071] Preferably, the first heat preservation time is 1 hour to 1.5 hours.
[0072] Preferably, the second heat preservation time is 2h to 2.5h.
[0073] Preferably, the cooling conditions are: cooling with the furnace to 90°C~100°C.
[0074] By determining the cooling temperature, thermal stress cracking of the negative electrode material can be avoided.
[0075] Preferably, the pickling conditions are as follows: the negative electrode material after the heat preservation is completed is immersed in a 3% dilute sulfuric acid solution for 4 to 6 seconds.
[0076] Preferred pickling conditions can remove the oxide layer on the surface of the negative electrode material and expose the active sites.
[0077] Preferably, the drying conditions are: vacuum drying at 80℃~90℃ to constant weight.
[0078] The negative electrode material provided by this invention, through the rational design of the composition and ratio of graphene-based composite materials, can effectively solve the problems of easy hydrogen evolution, insufficient conductivity and active material shedding in lead-acid battery negative electrodes, and significantly improve the cycle performance of the battery. Detailed Implementation
[0079] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0080] To better illustrate the present invention, further examples are provided below.
[0081] Example 1 This embodiment provides a graphene-based composite material, including a graphene-CNTs three-dimensional composite framework and tin dioxide and titanium dioxide loaded on the graphene-CNTs three-dimensional composite framework; The mass ratio of the graphene-CNTs three-dimensional composite framework, tin dioxide, and titanium dioxide is 97:5:1. The preparation method of the graphene-CNTs three-dimensional composite framework includes the following steps: S100. A 0.5 mm thick nickel foam with a porosity of 95% is placed in acetone and treated with ultrasonic treatment at 200 W and 40 kHz for 15 min. Then, it is annealed at 800 °C for 30 min under the condition that the volume ratio of H2 and Ar is 1:3. At 1000 °C, hydrogen is introduced at a flow rate of 50 sccm, methane at a flow rate of 20 sccm, and Ar at a flow rate of 520 sccm. Graphene is grown on the nickel foam by CVD method, and the growth time is controlled to be 10 min, to obtain a primary treated foam board. S200, at 60℃, the primary treated foam board was etched with an etching solution for 24 hours. After etching, the primary treated foam board was dialyzed to neutral using deionized water and then freeze-dried at -50℃ to obtain graphene. The etching solution was a mixed aqueous solution containing hydrochloric acid and ferric chloride, wherein the concentration of hydrochloric acid was 0.1 mol / L and the concentration of ferric chloride was 2.8 mol / L, and the mass ratio of the etching solution to the primary treated foam board was 10:1. S300, under Fe-Co catalyst conditions, acetylene was introduced at 700℃ with a flow rate of 20 sccm to grow carbon nanotubes on graphene for 10 min, resulting in a graphene-CNTs three-dimensional composite framework; the molar ratio of iron to cobalt was 1:1, and the mass ratio of Fe-Co catalyst to graphene was 2:100. This embodiment provides a method for preparing the above-mentioned graphene-based composite material, including the following steps: Step 1: Mix 0.1 mol / L ethanol-water solution containing SnCl2 and 0.025 mol / L ethanol-water solution containing Ti(SO4)2 thoroughly to obtain an ethanol-water solution containing SnCl2 and Ti(SO4)2. Then add the graphene-CNTs three-dimensional composite framework and polyvinylpyrrolidone. Adjust the pH to 3 with 0.1 mol / L hydrochloric acid solution, degas at -0.1 MPa for 2 h, then impregnate for 2 h. Release the pressure to atmospheric pressure at a rate of 0.01 MPa / min, and dry at -50℃ for 2.5 h to obtain the first-treated graphene-CNTs three-dimensional composite framework system. In the ethanol-water solution containing SnCl2 and Ti(SO4)2, the volume ratio of ethanol to water is 1:1, and the concentration of polyvinylpyrrolidone is 0.6 wt%. Step 2: At 5℃, the first-treated graphene-CNTs three-dimensional composite framework system was added to a 0.2 mol / L sodium borohydride solution and reacted for 1 h. After washing, it was annealed at 60℃ for 2 h, and then heated to 300℃ for oxidation reaction for 2 h to obtain graphene-based composite material. The mass ratio of the first-treated graphene-CNTs three-dimensional composite framework system to the boron-containing reducing agent solution was 1:10. This embodiment provides a negative electrode material, comprising the following components in parts by weight: 22 parts lead powder and 1 part graphene-based composite material; This invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: Graphene-based composite material, lead powder, and stearic acid were mixed evenly, with the amount of stearic acid added being 0.5% of the sum of the mass of graphene-based composite material and lead powder. The mixture was ball-milled at 500 rpm for 2 hours to ensure uniform dispersion of graphene-based composite material and lead powder. Then, the mixture was kept at 300℃ for 1 hour, heated to 320℃ and kept at 320℃ for 2.5 hours, cooled to 90℃ in the furnace, immersed in a 3% dilute sulfuric acid solution for 4 seconds, and dried at 80℃ to constant weight to obtain the negative electrode material.
[0082] Example 2 This embodiment provides a graphene-based composite material, including a graphene-CNTs three-dimensional composite framework and tin dioxide and titanium dioxide loaded on the graphene-CNTs three-dimensional composite framework; The mass ratio of the graphene-CNTs three-dimensional composite framework, tin dioxide, and titanium dioxide is 92:5:0.5. The preparation method of the graphene-CNTs three-dimensional composite framework includes the following steps: S100. A 1 mm thick nickel foam with a porosity of 95% was placed in acetone and treated with ultrasonic treatment at 500 W and 40 kHz for 18 min. Then, it was annealed at 810 °C for 35 min under the condition that the volume ratio of H2 to Ar was 1:3.5. At 1050 °C, hydrogen was introduced at a flow rate of 100 sccm, methane at a flow rate of 10 sccm, and Ar at a flow rate of 500 sccm. Graphene was grown on the nickel foam by CVD method, and the growth time was controlled to be 30 min, to obtain a primary treated foam board. S200, at 80℃, the primary treated foam board was etched with an etching solution for 12 hours. After etching, the primary treated foam board was dialyzed to neutral using deionized water and then freeze-dried at -50℃ to obtain graphene. The etching solution was a mixed aqueous solution containing hydrochloric acid and ferric chloride, wherein the concentration of hydrochloric acid was 0.3 mol / L and the concentration of ferric chloride was 3 mol / L, and the mass ratio of the etching solution to the primary treated foam board was 20:1. S300, under Fe-Co catalyst conditions, acetylene was introduced at 720℃ with a flow rate of 50 sccm to grow carbon nanotubes on graphene for 30 min, resulting in a graphene-CNTs three-dimensional composite framework; the molar ratio of iron to cobalt was 1:2, and the mass ratio of Fe-Co catalyst to graphene was 1:100. This embodiment provides a method for preparing the above-mentioned graphene-based composite material, including the following steps: Step 1: Mix 0.2 mol / L ethanol aqueous solution containing SnCl2 and 0.03 mol / L ethanol aqueous solution containing Ti(SO4)2 evenly to obtain an ethanol aqueous solution containing SnCl2 and Ti(SO4)2. Then add graphene-CNTs three-dimensional composite framework and polyvinylpyrrolidone. Adjust the pH to 2 with 0.2 mol / L hydrochloric acid aqueous solution, degas at -0.2 MPa for 2.5 h, then impregnate for 2 h. Release the pressure to atmospheric pressure at a rate of 0.02 MPa / min, and dry at -50℃ for 2.5 h to obtain the first-treated graphene-CNTs three-dimensional composite framework system. In the ethanol aqueous solution containing SnCl2 and Ti(SO4)2, the volume ratio of ethanol to water is 1:0.9, and the concentration of polyvinylpyrrolidone is 0.5 wt%. Step 2: At 0℃, the first-treated graphene-CNTs three-dimensional composite framework system was added to a 0.4mol / L sodium borohydride solution and reacted for 1.5h. After washing, it was annealed at 70℃ for 2.5h, and then heated to 320℃ for oxidation reaction for 2.5h to obtain graphene-based composite material. The mass ratio of the first-treated graphene-CNTs three-dimensional composite framework system to the boron-containing reducing agent solution was 1:20. This embodiment provides a negative electrode material, comprising the following components in parts by weight: 20 parts lead powder and 1 part graphene-based composite material; This invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: Graphene-based composite material, lead powder, and stearic acid were mixed evenly, with the amount of stearic acid added being 0.8% of the sum of the mass of graphene-based composite material and lead powder. The mixture was ball-milled at 600 rpm for 2.5 h to ensure uniform dispersion of graphene-based composite material and lead powder. Then, the mixture was kept at 280℃ for 1.5 h, heated to 340℃ and kept at 340℃ for 2 h, cooled to 100℃ in the furnace, immersed in a 3% dilute sulfuric acid solution for 6 s, and dried at 90℃ to constant weight to obtain the negative electrode material.
[0083] Example 3 This embodiment provides a graphene-based composite material, including a graphene-CNTs three-dimensional composite framework and tin dioxide and titanium dioxide loaded on the graphene-CNTs three-dimensional composite framework; The mass ratio of the graphene-CNTs three-dimensional composite framework, tin dioxide, and titanium dioxide is 95:7:0.5. The preparation method of the graphene-CNTs three-dimensional composite framework includes the following steps: S100. A 0.8 mm thick nickel foam with a porosity of 95% was placed in acetone and treated with ultrasonic treatment at 300 W and 40 kHz for 15 min. Then, it was annealed at 800 °C for 35 min under the condition that the volume ratio of H2 and Ar was 1:3. At 1020 °C, hydrogen was introduced at a flow rate of 80 sccm, methane at a flow rate of 15 sccm, and Ar at a flow rate of 500 sccm. Graphene was grown on the nickel foam by CVD method, and the growth time was controlled to be 20 min, to obtain a primary treated foam board. S200, at 70℃, the primary treated foam board was etched with an etching solution for 20 hours. After etching, the primary treated foam board was dialyzed to neutral using deionized water and then freeze-dried at -50℃ to obtain graphene. The etching solution was a mixed aqueous solution containing hydrochloric acid and ferric chloride, wherein the concentration of hydrochloric acid was 0.2 mol / L and the concentration of ferric chloride was 3 mol / L, and the mass ratio of the etching solution to the primary treated foam board was 15:1. S300, under Fe-Co catalyst conditions, acetylene was introduced at 700℃ with a flow rate of 40 sccm to grow carbon nanotubes on graphene for 20 min, resulting in a graphene-CNTs three-dimensional composite framework; the molar ratio of iron to cobalt was 1:1, and the mass ratio of Fe-Co catalyst to graphene was 0.5:100. This embodiment provides a method for preparing the above-mentioned graphene-based composite material, including the following steps: Step 1: Mix 0.15 mol / L of an ethanol-water solution containing SnCl2 and 0.03 mol / L of an ethanol-water solution containing Ti(SO4)2 thoroughly to obtain an ethanol-water solution containing SnCl2 and Ti(SO4)2. Then add a graphene-CNTs three-dimensional composite framework and polyvinylpyrrolidone (PVP). Add the graphene-CNTs three-dimensional composite framework and PPVP to the ethanol-water solution containing SnCl2 and Ti(SO4)2. Adjust the pH to 2 using 0.2 mol / L hydrochloric acid solution. Vacuum at -0.2 MPa for 2 hours, then impregnate for 2 hours. Release the pressure to atmospheric pressure at a rate of 0.02 MPa / min, and dry at -50℃ for 2.5 hours to obtain the first-treated graphene-CNTs three-dimensional composite framework system. In the ethanol-water solution containing SnCl2 and Ti(SO4)2, the volume ratio of ethanol to water is 1:1.1, and the concentration of PPVP is 0.5 wt%. Step 2: At 3℃, the first-treated graphene-CNTs three-dimensional composite framework system was added to a 0.4mol / L sodium borohydride solution and reacted for 1h. After washing, it was annealed at 65℃ for 2h, and then heated to 300℃ for oxidation reaction for 2.5h to obtain graphene-based composite material. The mass ratio of the first-treated graphene-CNTs three-dimensional composite framework system to the boron-containing reducing agent solution was 1:15. This embodiment provides a negative electrode material, comprising the following components in parts by weight: 20 parts lead powder and 1 part graphene-based composite material; This invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: Graphene-based composite material, lead powder, and stearic acid were mixed evenly, with the amount of stearic acid added being 0.8% of the sum of the mass of graphene-based composite material and lead powder. The mixture was ball-milled at 600 rpm for 2.5 h to ensure uniform dispersion of graphene-based composite material and lead powder. Then, the mixture was kept at 300℃ for 1.5 h, heated to 340℃ and kept at 340℃ for 2 h, cooled to 100℃ in the furnace, immersed in a 3% dilute sulfuric acid solution for 6 s, and dried at 90℃ to constant weight to obtain the negative electrode material.
[0084] Comparative Example 1 This comparative example provides a negative electrode material, the difference being that titanium dioxide is replaced with an equal amount of silicon dioxide; The other ingredients and steps are the same as in Example 1.
[0085] Comparative Example 2 This comparative example provides a negative electrode material, the difference being that tin dioxide is replaced with an equal amount of zirconium dioxide; The other ingredients and steps are the same as in Example 1.
[0086] Comparative Example 3 This comparative example provides a negative electrode material, the difference being that titanium dioxide is replaced with an equal amount of tin dioxide; The other ingredients and steps are the same as in Example 1.
[0087] Comparative Example 4 This comparative example provides a negative electrode material, the difference being that the preparation method of the negative electrode material is different, specifically including the following steps: Graphene-based composite material, lead powder, and stearic acid were mixed evenly. The amount of stearic acid added was 0.5% of the sum of the mass of graphene-based composite material and lead powder. The mixture was ball-milled at 500 rpm for 2 hours to ensure uniform dispersion of graphene-based composite material and lead powder. Then, it was kept at 300℃ for 3.5 hours and cooled to 90℃ in the furnace. The mixture was then immersed in a 3% dilute sulfuric acid solution for 4 seconds and dried at 80℃ to constant weight to obtain the negative electrode material. The other ingredients and steps are the same as in Example 1.
[0088] Application examples Negative electrode plate: The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-4 are mixed with carbon black, short fibers, water and sulfuric acid in a mass ratio of 80:1:0.5:9:9.5 to form an electrode paste. The electrode paste is evenly coated on a metal grid to form a 2.5 mm thick electrode plate. The coated electrode plate is dried at 150°C to remove moisture and solvent and harden the electrode plate.
[0089] Positive electrode plate: Lead oxide powder, carbon black, short fibers, water, and sulfuric acid are mixed in a mass ratio of 80:1:0.5:9:9.5 to form an electrode paste. The electrode paste is evenly coated onto a metal grid to form a 2.5 mm thick electrode plate. The coated electrode plate is dried at 150°C to remove moisture and solvent, making the electrode plate hard.
[0090] The positive and negative plates can be prepared using conventional methods, and the raw materials used are all commonly used materials in this field.
[0091] A 1.3M sulfuric acid solution was used as the electrolyte, and lead-acid batteries were assembled with the prepared negative and positive electrode plates. Batteries made with the negative electrode materials provided in Examples 1-3 were designated as Application Examples 1-3, and batteries made with the negative electrode materials provided in Comparative Examples 1-4 were designated as Comparative Application Examples 1-4. The capacity retention rate after 200 cycles of the batteries provided in Application Examples 1-3 and Comparative Application Examples 1-4 was measured, and the hydrogen evolution rate and internal resistance of the corresponding negative electrode plates were also measured. The specific testing methods are as follows: The test method for capacity retention after 200 cycles is as follows: GB / T 5008.1-2013; The hydrogen evolution rate is detected by the following method: constant current charging hydrogen evolution method; The method for detecting internal resistance is as follows: The internal resistance of the battery is measured using the AC injection method; The specific test results are shown in Table 1: Table 1
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A graphene-based composite material, characterized in that, It includes the following components: a graphene-CNTs three-dimensional composite framework and tin dioxide and titanium dioxide loaded on the graphene-CNTs three-dimensional composite framework; The graphene-CNTs three-dimensional composite framework is obtained by depositing carbon nanotubes on the graphene surface; The mass ratio of the graphene-CNTs three-dimensional composite framework, tin dioxide, and titanium dioxide is (92~97):(5~7):(0.5~1).
2. The graphene-based composite material as described in claim 1, characterized in that, The preparation of the graphene-CNTs three-dimensional composite framework includes the following steps: S100. Graphene is grown on a foam board using CVD at 1000℃~1050℃ to obtain a primary treated foam board. S200: At 60℃~80℃, the primary treated foam board is etched using an etching solution to obtain graphene. S300. Under bimetallic catalyst conditions, acetylene is introduced at 700℃~720℃ to grow carbon nanotubes on the graphene, thereby obtaining the graphene-CNTs three-dimensional composite framework.
3. A method for preparing the graphene-based composite material according to any one of claims 1 to 2, characterized in that, Includes the following steps: Step 1: Add the graphene-CNTs three-dimensional composite framework and nonionic surfactant to an ethanol aqueous solution containing soluble tin salt and soluble titanium salt, adjust the pH to acidic, impregnate at -0.2MPa~-0.1MPa, release the pressure, and dry at low temperature to obtain the first-treated graphene-CNTs three-dimensional composite framework system. Step 2: At 0℃~5℃, the first treated graphene-CNTs three-dimensional composite framework system is added to a boron-containing reducing agent solution for reaction, washed, annealed at 60℃~70℃, and then heated to 300℃~320℃ for oxidation reaction to obtain graphene-based composite material.
4. The method for preparing the graphene-based composite material as described in claim 3, characterized in that, In step 1, the soluble tin salt is SnCl2; In step 1, the soluble titanium salt is Ti(SO4)2; The amount of the nonionic surfactant added is 0.5% to 0.6% of the mass of the ethanol aqueous solution containing soluble tin salt and soluble titanium salt; In step 1, the soaking time is 2 hours to 2.5 hours; In step 1, the drying temperature is -50℃ to -48℃, and the time is 2h to 2.5h.
5. The method for preparing the graphene-based composite material as described in claim 3, characterized in that, In step 2, the boron-containing reducing agent solution is a sodium borohydride solution; In step 2, the reaction time is 1 h to 1.5 h.
6. The method for preparing the graphene-based composite material as described in claim 3, characterized in that, In step 2, the mass ratio of the first treated graphene-CNTs three-dimensional composite framework system to the boron-containing reducing agent solution is 1:(10~20), and the concentration of the boron-containing reducing agent solution is 0.2mol / L~0.4mol / L; In step 2, the annealing time is 2 hours to 2.5 hours. In step 2, the oxidation reaction takes 2 to 2.5 hours.
7. A negative electrode material, characterized in that, The composition comprises the following components in parts by weight: 20-22 parts of lead powder and 1 part of the graphene-based composite material as described in claims 1-2 or the graphene-based composite material prepared by the method described in any one of claims 3-6.
8. A method for preparing the negative electrode material according to claim 7, characterized in that, Includes the following steps: The graphene-based composite material and lead powder are mixed evenly, and the mixture is kept at 280℃~300℃ for the first heat preservation. Then, the temperature is raised to 320℃~340℃ for the second heat preservation. After cooling, acid washing, and drying, the negative electrode material is obtained.
9. The method for preparing the negative electrode material as described in claim 8, characterized in that, The first heat preservation time is 1 hour to 1.5 hours; The second heat preservation time is 2h~2.5h.
Citation Information
Patent Citations
Carbon nano tube freeze drying body / metal oxide compound
CN103213966A
Method for preparing flexible stannous oxide nano sheet / carbon nanotube-graphene three-dimensional composite material
CN104617274A
Current collector of lead-acid storage battery
CN106876718A
Carbon-based energy storage material with multilevel structure and preparation method of carbon-based energy storage material
CN117638034A